Lecturer Performance Decision Support System Using The TOPSIS Method Based on Web - Suandi Daulay (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2020)
AMIK Mahaputra is one of the private computer colleges in the city of Pekanbaru. In increasing its resources, this university conducts performance appraisals of lecturers and employees. This performance assessment will form the basis of promotion. At present, the system in assessing its performance still has weaknesses, namely by improper lecturers or employees who occupy certain positions and positions. The purpose of this study is to later be able to make it easier to give a decision on the performance evaluation of lecturers and employees each year as part of the process of career development and promotion. The data obtained include the assessment of lecturers by students, the discipline of lecturers on giving lectures, the allocation of time by each lecturer and the method used is TOPSIS where this method is considered suitable for this research. and AMIK employees Mahaputra pekanbaru. Decision support system for evaluating the performance of lecturers and employees in promotion. Although the decision taken has been 74% but it has been recommended to assist the management of AMIK Mahaputra in making decisions.